Essays on decomposition of output growth and Total Factor Productivity (TFP) in Sub-Saharan Africa and South Africa’s nine provinces - Green, Christian Floris (My University, 2022)
International experience has revealed that countries (national level) and the regions in a country (sub-national level) grow at different rates. Explaining the difference in these growth rates and identifying the sources of this growth have been the focus of growth theory, i.e., neoclassical (exogenous) growth theory advanced by Solow (1956) and Swan (1956) and new (endogenous) growth theory introduced by Romer (1986) and Lucas (1988). Underpinned by these two growth theories, numerous economic studies have established that the difference in growth rates at a national and sub-national level can be attributed to factors such as institutional quality, financial development and human capital (health), while the sources of growth are physical capital, human capital (education), labour, and Total Factor Productivity (TFP). However, the standard growth accounting and cross-country analyses, the empirical techniques of neoclassical and new growth theories do not adequately clarify the sources of growth and their relative impact. The three essays of this PhD thesis use Stochastic Frontier Analysis (SFA), as an alternative empirical technique, to address these limitations. This PhD thesis thus contributes to the growth literature on the importance of the different factors [specifically, institutional quality, financial development and human capital (health)] to the growth rate and the relative importance of the different sources of growth at a national and sub-national level. The growth elements in Sub-Saharan Africa (SSA) (national level) and South Africa’s nine provinces (subnational level) are decomposed through the use of SFA to establish: (i) in Essay 1, that Financial Development (FD) impacts on Technical Efficiency (TE) through Institutions (I), with banking development more important than stock market development in contributing to financial development and consequently increases in productive efficiency, in SSA; (ii) in Essay 2, that in contrast to the established growth literature, physical capital accumulation is more important than TFP in driving the growth in South Africa’s nine provinces and (iii) in Essay 3, that consistently with the literature, health (public health expenditure) has a significant impact on the Technical Efficiency (TE) of South Africa’s nine provinces. To allow the financial sector (banks and stock exchanges) to play its catalytic role in facilitating productive efficiency and economic growth in SSA, policy makers should ensure an appropriate institutional environment (e.g., addressing issues of property rights and government effectiveness). For growth to be sustainable in South Africa’s nine provinces, each provincial government should increase the relevant capital investments [e.g., public sector Gross Fix Capital Formation (GFCF)] and invest in productivity enhancing factors (e.g., human capital, both education and health) that would enrich its growth potential based on its unique requirements.
A thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law and Management, University of the Witwatersrand, 2022
Keywords: Total Factor Productivity (TFP); Sub-Saharan Africa; Output Growth